ONTOLOGI PENDIDIKAN KARAKTER PERSPEKTIF RATNA MEGAWANGI DALAM PENGUATAN PERKEMBANGAN KOGNITIF ANAK USIA DINI - Laili Khairul; Ichsan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Character education is a deliberate effort to instill moral values and goodness in children from an early age to form wise and responsible individuals. Ratna Megawangi's perspective emphasizes the importance of character education as the main foundation in strengthening the cognitive development of early childhood. Character education according to Megawangi includes nine main pillars, including love for God and His creations, responsibility, honesty, respect, mutual cooperation, self-confidence, leadership, humility, and tolerance and love of peace. This character education is holistic and continuous, involving family, school, and community, and has strong relevance to the principles of Islamic education. By instilling character from an early age, children not only develop morally but also cognitively, so that they are able to face the challenges of learning and life optimally. This study uses a literature approach to examine Ratna Megawangi's thoughts and their relevance in the context of early childhood education.